Literatura a religia. O potrzebie religioznawczej refleksji w obrębie literaturoznawstwa - Jocz, Artur (Wydawnictwo Fundacji Humaniora, 2013)
Literature and religion. On the need for religious studies reflection in the sphere of literary studies. Today, no one is surprised by a philosophical reflection on religion. Are the relations between literature and religion similarly attractive in terms of cognition, as well? Is it worth anything to deliberate on the issue of incorporating literature into the sphere of the scientific interests of specialists in religious studies at all? Therefore, the aim of considerations herein is not only an attempt to indicate the ways of recognising the processes in question using the apparatus of religious studies, but also an intention to consider the chance for possible support of the efforts undertaken by literary scholars. Due to the character of the sketch herein, the ascertainment contained in it only signals the existence of a more complex research project. It has been conceived as a certain reflection on the phenomenon of the reception of gnosis, Gnosticism and Neo-Gnosis in literature.
Keywords: religion; literature; religious studies; literary studies